Cryptoization and Shadow Currency: Legal Overview of the Importance of Digital Rupiah in Indonesia - Sulistiyono, Adi; Kharisma, Dona Budi (Faculty of Law, Universitas Pekalongan, 2024)
Cryptoization in Indonesia can be seen in the number of investors and crypto asset transactions. As of January 2024, the total number of crypto asset investors reached 18.83 million investors. Meanwhile, the total accumulated value of crypto asset transactions throughout 2024 was recorded at IDR 48.82 trillion. Various types and developments in crypto assets trigger shadow currency risks. Shadow currency is a currency function that can be replaced by another form. In this regard, research is needed regarding the relationship between crypto assets as shadow currency in financial stability and the importance of regulating digital rupiah in Indonesia. The approach used is the statute approach. This research will examine various laws and regulations relating to crypto assets, fintech, financial systems and currencies. The research results show that the crypto asset transaction process occurs outside the official monetary system and can develop into a digital currency area outside certain jurisdictions. The materialization of this risk can threaten a country's monetary sovereignty, thus triggering the risk of shadow currency. Therefore, it is recommended that the Digital Rupiah be a Central Bank Digital Currency (CDBC) which is officially implemented in Indonesia. However, there needs to be regulatory and policy support needed so that CBDC can be implemented in Indonesia, one of which is through a revision of the Indonesian Act on Currency.